Karakteristik Kecelakaan Lalu Lintas pada Jalan Tol Jagorawi km 19–km 40 Kabupaten Bogor - Endang Widjajanti (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2021)
The aims of this research are to identify accident characteristics and blackspot on Jakarta – Bogor – Ciawi (Jagorawi) Toll Road km 19 – km 40, as part of Jagorawi Toll Road, using secondary data on traffic accidents for 3 years, namely 2016 – 2018. The research method refers to Pd T-09-2004-B-Guidelines for Handling Traffic Accident Black Sites (Directorate General of Bina Marga, 2004). The results showed the most accidents for Bogor direction occurred on Friday (39%) and for Jakarta directions on Tuesday (22%), in bright light conditions, fair weather with the dominant accident type of rear front crash (81%). The blackspots of Jagorawi Toll Road are located on the Km 23 (km 23+090, 23+600 and 23+800) and km 26 (km 26+200, 26+800 and 26+870) for Bogor direction and km 23 (km 23+200, 23+400, 23+600) for Jakarta direction. The proposed handling is the addition of warning signs in blackspot areas, safe distance limits and speed limits on toll roads.